ABU NASR FARABI’S IDEAS ABOUT RELIGION - Abdufattayeva Shahrizoda Shuhratbek qizi (European Science Publishing, 2023)
This article reflects the interaction between philosophy, religion and politics by revealing the role and rank of religion within the hierarchical system of al-Farabi's political philosophy. Also, his attitude to religion, ideas of religious openness are reflected.
Keywords: Abu Nasr Farabi, philosophy, religion, politics, milla, “Kitābu al-milla”, “Kitābu al-huruf”, jihad, hijrah, shari'a, fiqh, 'Imām, Neo-Platonic, Isma'ilism, Sufizm.